A truncated matrix variate gamma distribution - Shokofeh Zinodiny; Saralees Nadarajah; Daya K. Nagar (Results in Applied Mathematics, 2024)
A truncated form of a matrix variate gamma distribution is introduced and a number of properties of this distribution such as cumulative distribution function, orthogonal invariance, moment generating function, marginal distribution of block matrices, and moments are derived. Some results on distribution of random quadratic forms are also derived.